The sensorial structures of Spondylus americanus Hermann,1781 (Mollusca: Bivalvia, Spondylidae) - Marina Gomes Viana; Cristina de Almeida Rocha-Barreira (Brazilian Archives of Biology and Technology, 2007)
Adult animals of Spondylus americanus were analyzed and specialized sensorial structures, the sensorial papillae and the eyes, were characterized. The sensorial papillae were projections on the edge of the mantle in form of light brown fingers which had function of percepting stimulus coming from the medium. They were constituted by loose conjunctive tissues with longitudinal muscular fibers and externally covered by ciliated cubic epithelium, which presented high amount of melanocytes that gave the coloration of the papillae. The eyes were more complex, being on small stalks histologically similar to the papillae. They exhibited a circular formate and had a metallic blue color. Theses structures were constituted by a corneo epithelium, cornea, lens, retina, basal stalk, periocular band and optical nerve. The eyes were distributed asymmetrically to both valves related with the sedentarism of the species. Right valve presented a smaller number of eyes when compared to left one. Foram examinados exemplares adultos de Spondylus. americanus Hermann, 1781 e estruturas especializadas na percepção de estímulos foram caracterizadas: as papilas sensoriais e os ocelos. As papilas sensoriais são projeções do bordo manto em forma de dedos de cor castanha e com a função de perceber estímulos vindo do meio, são constituídas por tecido conjuntivo frouxo contendo fibras musculares longitudinais e revestidas externamente por epitélio cúbico ciliado, o qual apresenta grande quantidade de melanócitos, que dão a coloração das papilas. Os ocelos são mais complexos, estando sobre pequenos pedúnculos histologicamente semelhante às papilas, têm formato circular e possui cor azul metálica. Constituí-se por um epitélio córneo, córnea, lente, retina, pedúnculo basal, banda periocular e nervo óptico. Os ocelos distribuem-se assimetricamente por ambas as valvas, o que está relacionado com o sedentarismo da espécie. A valva direita apresenta menor número de ocelos quando comparada a esquerda.